MAKNA VERBA NERAU DAN MEZASU DALAM SINONIM BAHASA JEPANG - I Gusti Ayu Regina Dhira; Ni Wayan Meidariani; Wahyu (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2025)
Japanese is a foreign language with a wide variety of words. One such variation is in the verb class. This article discusses the meaning and use of the verbs